Follow-up of infants with congenital syphilis during the penicillin shortage period - Ana Fátima Braga Rocha; Maria Alix Leite Araújo; Ana Karinne Dantas de Oliveira; Lucas Fernandes de Oliveira; Lea Dias Gomes Vasconcelos Pimentel; Adriana Lopes Lima Melo (Jornal de Pediatria, 2023)
Objective: To analyze the follow-up, in specialized outpatient clinics, of infants reported with congenital syphilis during the penicillin shortage. Method: A cross-sectional study was carried out in ten public maternity hospitals affiliated with the Brazilian Unified Health System in the city of Fortaleza, state of Ceará. Clinical records of infants reported with congenital syphilis who were born alive in 2015 were used to describe correlates of attendance at recommended clinical follow-up appointments. Results: A total of 469 infants reported with CS from January 1/2015 to December 31/2015 were included in the analysis. The results show that most infants did not attend the follow-up visits (368/469, 78.5%) and the main associated factors are that the follow-up clinic is located in a different hospital from that where the infant was born (OR: 3.7; CI: 2.20–6.22; p < 0.001) and the use of illicit drugs by the mother (OR: 3.2; CI: 1.57–6.87; p = 0.002). Only 33.7% (34/101) were followed until discharge. Conclusion: The majority of infants with reported congenital syphilis during this period did not attend the follow-up visits. Public health efforts aimed at reaching the parents of infants with CS should be a priority to ensure appropriate clinical identification and management of the associated outcomes of this vertically transmitted infection.